THE EFFECT OF PROFITABILITY, LIQUIDITY, LEVERAGE AND FIRM SIZE TOWARD BOND RATING ON NON FINANCIAL INSTITUTION LISTED IN INDONESIA STOCK EXCHANGE PERIOD 2010-2014 - Mardiyati, Umi; Nur Utami, Sekar Ghita; Ahmad, Gatot Nazir (Fakultas Ekonomi, Universitas Negeri Jakarta, 2015)
The Purpose of this research is to know the effects of profitability, liquidity, leverage, and firm size toward bond rating. This research used logistic regression as a method of data analysis. The samples of this research are non financial firms listed in Indonesian Stock Exchanged and rated by PEFINDO’s rating agency period 2010-2014. In this research, bond rating as dependent variabel categorized into investment grade (1) and non investment grade (0), while the independent variabels consisted of profitability proxied by ROA, liquidity proxied by CR, leverage proxied by DER, and firm size proxied by total asset. The result research as parsial show that profitability and leverage has positive and significant effect on bond rating, while liquidity and firm size has positive but not significant effect on bond rating. While as simultan profitability, liquidity, leverage and firm size has positive and significant effect on bond rating. Key word: profitability, liquidity, leverage, firm size, bond rating.